Types of moulding and methods of eliminating dry rot in historic buildings: example of Sobiescy Palace in Lublin (based on study by Mirosław Zaród) = Zagrzybienia i metody odgrzybiania obiektów zabytkowych na przykładzie Pałacu Sobieskich w Lublinie (na podstawie opracowania dokonanego przez M. Zaróda) - Wrana, Jan; Jarocka-Mikrut, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
By presenting Sobiescy Palace in Lublin as well as results of mycological research conducted in the said premises, the authors describe hazards and dangers arising from damp present in historic buildings for a long time. Results of mycological research quoted in this article indicate that differences in levels of damp depend on the cardinal direction a specific wall faces.
Keywords: Pałac Sobieskich (Lublin); Lublin; zagrzybienia obiektów budowlanych; zawilgocenia; Sobiescy Palace; mould in buildings; damp